Synergistic effect of surface modification of carbon fabrics and multiwall carbon nanotube incorporation for improving tribological properties of carbon fabrics/resin composites. Issue 1 (23rd July 2019) - Wang, Beibei; Fu, Qiangang; Li, Hejun; Qi, Lehua; Lu, Yuanyuan
Abstract: Surface modification of carbon fabrics (CFs) by nitric acid and multiwall carbon nanotube (MWCNT) incorporation into the resin matrix were simultaneously applied for CFs/resin composites to improve their tribological properties. The results show that surface roughness (Ra) of CFs increases from 8.20 to 15.10 nm after nitric acid treatment due to the remove of sizing agent on CFs surface. Surface hardness of the composites with 0.1 wt% MWCNT (CFR‐H‐0.1%T) is enhanced from 0.745 to 1.216 GPa compared with that of untreated CFs/phenolic resin composites (CFR), which is attributed to the toughening effect of MWCNT in resin matrix. The friction coefficient increases from 0.10 for CFR to 0.16 for CFR‐H‐0.1%T, while the wear rate significantly decreases from 5.75 × 10 −14 m 3 (N m) −1 to 2.05 × 10 −14 m 3 (N m) −1 . The improvement of friction and wear properties is ascribed to the synergistic effect of the oxidation etching of nitric acid and the strengthening and toughening of MWCNT.